The current state of oral epic performing in the Philippines and ways of transmitting / acquiring sacred knowledge by singers and shamans - M. V. Stanyukovich (Шаги)
How do the ritual oral epics of the indigenous survive today in a highly westernized Christian country? The paper gives an overview of the current situation in the Philippines based on 30 years of fieldwork with the Yattuka and Tuwali Ifugao hudhud singers, compared to the data of fellow researchers of Mindanao and Panay oral traditions and interviews taken during field trips to Tboli, Sama Bajaw and Panay Bukidnon. The unique value of the Philippine situation is that it allows us to witness processes that can be only hypothetically reconstructed for most of world epics, such as: change, transformation and /or elimination of ritual connections of the epic, of ritual functions of the performance and the performer, conversion of ritual texts into oral literature for «entertainment». «Songs for gods» that were previously addressed to spirits in order to please them and gain their help, are being transformed into «songs for humans»; «deep words» of sacred ritual language are largely replaced by more common ones. Notwithstanding, the process of transmitting/acquiring the sacred knowledge of epic singing is still very much alive; it is basically similar to that of a shaman or a healer. In both cases learning from the elders is employed, but the tradition often does not concentrate on that, focusing on the notion of a sacred gift, received by an epic singer/shaman (usually in a dream) from the «epic owners»: dead or dying singers, ancestors and/or deified epic heroes. The process of formation of a new epic performer often implies «shamanic illness» at the very start and emergency replacement of an older singer at a later stage. Parallels between the formation of an epic singer and a shaman/healer are illustrated by field materials collected in the Philippines (1995–2024) and among the Bahnaric indigenous groups of Cambodia (2015–2024).